Narrativa deportiva digital y su incidencia en la hinchada de clubes nacionales - Mejía Drouet, Kelly Daniela (2022)
In the development of this research work, an analysis of the sports programs broadcast by digital media in Ecuador is carried out. Therefore, surveys, interviews and analysis of files of the most relevant programs before and after the shipyard classics were carried out. The first chapter starts by defining the problem of this investigation, evidencing that the type of language used by the journalists of these programs can influence the actions of their fans, either positively or negatively, according to the opinions expressed during the development of the same.,,,,,